The Impact of ISO 27001 Implementation, Leasing Adoption, and Customer Trust on Data Center Leasing Decisions - Aditya Dyan Permadi; Laura Lahindah (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the impact of ISO 27001 implementation, risk management, and customer trust on data center leasing decisions. In an increasingly digital era, information security has become a critical factor in maintaining customer trust and satisfaction. This study uses a quantitative approach with a survey method through questionnaires distributed to data center customers. The results of the study show that the implementation of ISO 27001 significantly affects data center leasing decisions. Good risk management also has a positive impact on leasing decisions, while customer trust plays an important role in retaining and attracting new customers. These findings affirm that data center companies need to continuously strengthen their information security management systems to enhance customer trust and loyalty. This study provides practical contributions to data center companies in implementing and improving information security standards as well as providing academic insights into the literature on information security.